Use of Insecticide Treated Nets among Households with Children Under Five Years in Agotime-Ziope District - Abiwu, V.A. (University Of Ghana, 2018)
Background: Malaria remains a major cause of illness and death globally especially in malaria endemic countries. With substantial increase in funding for malaria control programs, countries in Sub Sahara Africa scaled up delivery of insecticide treated bed nets to households, increasing number of households owning ITNs and expectation of reduced malaria. ITN was identified as a verified useful and cost-effective tool for malaria prevention through consistently use by beneficiaries. However, utilization comparatively remains low. The study explored the current use of ITNs, assessed the household perception associated with ITNs and factors that influence households with children under five years to use the nets in the Agotime-Ziope District of Ghana. Methods: A qualitative study was employed adopting five FGD sessions and ten IDIs to collect information from heads or spouse of households drawn from five communities. Data was analysed using QSR NVivo 10 data analysis software according to the framework for conducting thematic analysis and captured themes that emerged from the data. Result: Findings revealed that majority of households have very good knowledge about malaria and its causes; were aware of ITN as the best measure for preventing malaria and also have experienced ITN use. Reasons that motivated users of ITNs included health improvement noting the severity of malaria; economic benefits regarding cost saving weighing the cost of treatments with that of prevention; maintenance of peace and tranquility in the family; contentment; and uptake of ITN use as habit. Non-enthusiastic users of ITNs noted perceived discomfort, ineffectiveness of ITNs to protect them against bites of mosquitoes, perception that mosquitoes are not always available and inability to hang nets because of its shape and limited space at sleeping places. No known cultural taboo or social restriction exist in the communities that prohibition ITN use but gender issues have implications for ITN use. Conclusion: Though ITN use is accepted to prevent malaria, some households remain adamant to adopt its use. Interventions should intensify sensitization targeted at household heads to recognize the severity of malaria, demystify the unscientific and personal sentiments against ITN use and reinforce the positive sentiments, with community engagement that support designing culturally acceptable messages. Monitoring strategies to visit homes encouraging consistent bed nets use and development of culture of ITN use especially among the young people is critical.
MPH.
Keywords: Insecticide; Households; Agotime-Ziope District; Nets